Quality Function Deployment in Healthcare: Systematic Literature Review - Sukma, Dias Irawati; Stiawan, Indra; Kurnia, Hibarkah; Purba, Humiras Hardi (Spektrum Industri, 2022)
More specific knowledge about Quality Function Deployment (QFD) has grown rapidly. There are many studies on the application of QFD in various industrial sectors including manufacturing, construction and services. QFD is a tool that can be used to assist companies in improving services by translating consumer desires into the technical characteristics of the company. This paper aims to provide a broad understanding and knowledge of the application of QFD in the healthcare industry. The approach used is Systematic Literature Review. This paper involves a review study of various papers from well-known databases related to the implementation of QFD in the healthcare industry. This paper provides benefits for researchers and practitioners to add insight and references for studies related to QFD in health services